WACANA HUMOR DALAM MEME DI MEDIA ONLINE SEBAGAI POTRET KEHIDUPAN SEBAGIAN MASYARAKAT INDONESIA - Ari Listiorini (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study aims to describe themes and topics, implicatures, and language aspects in humor discourse in memes in online media. The study employed the descriptive researchdesign. The data sources were 70 memes in four sites of online meme media, i.e. www.memecomicindo.com,www.indomeme.com, www.memecomic.id, and www.1cak.com.The results of the study are as follows. First, there are four meme themes in online media;they are social, political, legal, and religious themes. Second, there are three implicatures inmemes in online media, namely insinuation, suggestion, and the combination of insinuationand suggestion. Third, there are two language aspects that support implicatures and resultin humor in memes, namely the phonological and semantic aspects. The phonologicalaspect includes the repetition of sounds which in literature is often called a rhyme. Thesemantic aspect comprises the repetition of words and the use of similes, metaphors,hyperboles, personifications, syllogisms, abbreviations, and proverbs.Keywords: themes, topics, implicatures, language aspects, memes